Inovasi BAZNAS Purbalingga Dalam Meningkatkan Kesadaran Masyarakat Tentang Zakat - Pramono, Cita Zahra; Suyuti, Muh Hikamudin (PUSDATIN Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This research aims to analyze the management innovation applied by BAZNAS Purbalingga in increasing public awareness of zakat. Poverty is a fundamental problem in Indonesia, and zakat has great potential as an economic instrument to help alleviate poverty. Through a qualitative approach, data was collected from interviews with BAZNAS Purbalingga administrators and observations of their activities. The results of this study show that BAZNAS Purbalingga applies various effective management innovations, including careful program planning, structured organization, social program mobilization, and strict supervision. Programs such as socialization, the establishment of Zakat Collection Units (UPZ), and the use of digital technology succeeded in raising public awareness about the importance of giving zakat.